Consistency, Accuracy and Sensitivity of DEEA Gestdect Pregnancy Test in Cows - Samsudewa, D; Lukman, A; Sugiyanto, E; Setiatin, ET (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The aim of the research was to know the consistency, accuracy and sensitivity of DEEA Gestdect pregnancy test. The materials used in this research were urin samples from 322 cows, DEEA Gestdect pregnancy test kit, sticker, stop watch, colour list, harness, reaction tube and pipette. DEEA Gestdect pregnancy test was compared to palpation method. Descriptive and chi-square analysis was used in this research. The results showed that consistency, accuracy and sensitivity of DEEA Gestdect pregnancy test were 87.27%; 87.58% and 2 weeks of gestation period, respectively. It was concluded that DEEA Gestdect is a reliable pregnancy test in term of its consistency, accuracy and sensitivity. (Animal Production 10(1): 12-15 (2008)Â Key Words: Pregnancy test, DEEA Gestdect, Cow